2012
DOI: 10.1111/1567-1364.12020
|View full text |Cite
|
Sign up to set email alerts
|

Salt and oxidative stress tolerance inDebaryomyces hanseniiandDebaryomyces fabryi

Abstract: We report the characterization of five strains belonging to the halotolerant highly related Debaryomyces hansenii/fabryi species. The analysis performed consisted in studying tolerance properties, membrane characteristics, and cation incell amounts. We have specifically investigated (1) tolerance to different chemicals, (2) tolerance to osmotic and salt stress, (3) tolerance and response to oxidative stress, (4) reactive oxygen species (ROS) content, (5) relative membrane potential, (6) cell volume, (7) K(+) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Debaryomyces hansenii and D. fabryi are halotolerant/ halophilic yeasts (Neves et al, 1997;Prista et al, 1997;Mich an et al, 2012). The ability of wild strains from these species to live and multiply in the limit of salt solubility resides, namely, at the level of plasma membrane, which has substantially different properties as compared to S. cerevisiae (Kaneko et al, 1975;Tunblad-Johansson & Adler, 1987;Blagovic et al, 2001;Turk et al, 2007a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Debaryomyces hansenii and D. fabryi are halotolerant/ halophilic yeasts (Neves et al, 1997;Prista et al, 1997;Mich an et al, 2012). The ability of wild strains from these species to live and multiply in the limit of salt solubility resides, namely, at the level of plasma membrane, which has substantially different properties as compared to S. cerevisiae (Kaneko et al, 1975;Tunblad-Johansson & Adler, 1987;Blagovic et al, 2001;Turk et al, 2007a,b).…”
Section: Discussionmentioning
confidence: 99%
“…This result supports our previous observations from the qualitative experiment that showed that at certain high concentrations of NaCl, D. hansenii may have a special halotolerance mechanism that allows this strain to live in higher NaCl concentrations. It may also provide D. hansenii a higher tolerance ability to hyperosmotic environments than the same species isolated elsewhere (Aggarwal and Mondal, ; Michán et al ., ). This high osmotolerance ability might be significant in the survival of desert plants that grow in the salty soils during the dry summer.…”
Section: Discussionmentioning
confidence: 97%
“…(i) Toxic biogenic amines can be found in dry fermented sausages at relevant concentrations, and the amounts of these amines have been previously related to both temperature and NaCl in salami due to their influence on the lactic acid bacteria populations [45]. (ii) Although Debaryomyces has been reported as a halotolerant yeast, this character significantly varies between strains belonging to the same species [46]. (iii) Finally, D. hansenii is relatively sensitive to high temperatures.…”
Section: Evaluation Of Resistance Of Isolated Yeast Strains Under Difmentioning
confidence: 99%